Otolith Microstructure in Young-of-the Year Dolly Varden, Salvelinus malma, from American and Asian Populations: Resolution of Comparative Life History Characteristics - Radtke, R.L.; Fey, D.P.; DeCicco, A.F.; Montgomery, A. (ARCTIC, 1996)
Sigittal otoliths from young-of-the-year Dolly Varden, Salvelinus malma, captured from Cripple River, Alaska and Cha'atam River, Russia were prepared and observed with transmitted light microscopy. Distinct microstructure in samples from both locations indicated daily growth increments, hatching checks and first feeding checks that confirm literature findings in other salmonids. We used increment counts to estimate the ages of individual juveniles and calculated hatch dates and times of first feeding from those ages. Increments deposited before the first feeding mark were significantly smaller then those formed after this mark. Alaskan and Russian fish showed a significant difference in hatching times and the period of first feeding. Summer growth rates of the Russian population, calculated from length-at-the-age data, were faster (0.356 mm/day) than those of the Alaskan population (0.301 mm/day). However, when the average growth rate was calcualted with the formula GR=(Lcapture-Lhatching)/age, the values were higher for the Alaskan population (0.25 mm/day) than for the Russian population (0.20 mm/day). When otolith radius-fish size relationships were estimated, Alaskan otoliths were found to be larger for the same size fish, because wider increments were deposited in fish from Alaska. Increment width also was related to time of the year: wider increments were deposited during the warmer months. Otolith microstructure provided insights into the early life history of young-of-the-year Dolly Varden from American and Asian populations. Des sagittas provenant de Dolly Varden (Salvelinus malma) de l'année capturées dans la Cripple en Alaska et dans la Cha'atam en Russie ont été préparées et étudiées au microscope pour examen par transmission. Une microstructure distincte dans les échantillons provenant des deux sites révélait une croissance quotidienne, des repères de l'éclosion et des repères de la première phase alimentaire, qui confirment les résultats consignés dans la documentation sur d'autres salmonidés. On ...